Analisis Kebutuhan Perancangan Website Pelayanan Administrasi untuk Mahasiswa - Rahmi Pratiwi; Winanda Amilia; Luthfiani Luthfiani (Postgraduate, University of Mataram, 2023)
Administrative services to students play an important role at the university. Optimal administrative services to students can increase university competitiveness. One effort that can be made is to provide digital and online based service facilities to make the service process easier. However, currently, there are still administrative services at universities that are not digital and online based, which causes problems. The research method starts from requirements and analysis. The aim of the research is to analyze needs for problems in the field as a reference for designing administrative service websites for students. Data were collected using questionnaires and interviews at Educational Technology Study Program, Universitas Negeri Padang. The research results show that students need website-based administration services to handle the administration of letters to departments. The results of this research provide a solution for study programs to the problems they face